Evaluation of the adherence of ceramic tiles applied as facade lining - Valentini, P.; Kazmierczak, C. S. (Revista ALCONPAT, 2016)
The most serious pathology in ceramic tile is detachment because of the risk of accidents due to fall and the cost of repair. This research aims to evaluate the influence of ceramic plates applied with two types of adhesive mortar subjected to three different curing conditions (established by the ABNT 14081-4:2012) on the adhesion to the coating system. It was observed that cure is the variable with higher influence on the adhesive strength, followed by the type of adhesive mortar, while the water absorption of ceramic plate has a little influence on the results. Keywords: adherence; ceramic tiles; adhesive mortar